The Analysis Between Batak Toba and English In Question Words - Ade Armando; Danny Boy Damanik; Surya Ningsih Pakpahan; Ravika Siregar; Anita Sitanggang (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
The purpose of this research is to identify the similarities and differences between English and Toba Batak question terms. Qualitative descriptive research method. Methods of data collection including documentation. Descriptive analysis is used by researchers to examine the data. There are 5 question words in English: "What", "Where", "Who", "How", and "Why". There are seven interrogative words in the Toba Batak language: "Aha", "Ise", didia, ,"Boasa, "Boha, Piga, Beha." The findings of this study are to reveal six correlations or similarities between English and Toba Batak words. test.However, there are also differences between question words in English and Toba Batak.